Education strategies are the most commonly used in pediatric rehabilitation implementation research: a scoping review - Sahar Ghahramani; Sophia C. Larson; Allison J. L’Hotta; Kelly M. Harris; Kim Lipsey; Elvin H. Geng; Lisa A. Juckett; Catherine R. Hoyt (Implementation Science Communications)
Abstract Background Approximately one in six children has a disability, and effective, evidence-based rehabilitation can ameliorate the impact of these conditions over the lifespan. However, implementing interventions in real-world settings remains a challenge. This scoping review aimed to summarize the characteristics, implementation strategies, and outcomes of implementation studies in pediatric rehabilitation. Methods A comprehensive search was conducted in PubMed/MEDLINE, EMBASE, CINAHL, SCOPUS, and Web of Science from the database inception to December 2, 2022. Studies testing implementation strategies in pediatric rehabilitation interventions were included. Data extracted included study characteristics (e.g., country, intervention type, field of rehabilitation), implementation strategies characterized using the Expert Recommendations for Implementing Change taxonomy, and outcomes based on the Implementation Outcomes Framework. Results Of the 11,740 studies identified, 44 met the inclusion criteria. Most studies were conducted in the United States (n = 15, 34%) or Canada (n = 10, 23%) and used a mixed-methods design (n = 13, 30%). Interventions primarily targeted motor skills (n = 19, 43%) and were conducted in outpatient settings (n = 14, 32%) or homes (n = 11, 23%). The most commonly used implementation strategies were “train and educate key informant” (n = 21, 48%) and “use evaluative/iterative strategies” (n = 19, 43%). Feasibility (n = 19, 43%) and acceptability (n = 16, 36%) were the most frequently targeted implementation outcomes. Conclusions Reporting implementation strategies and outcomes in pediatric rehabilitation studies is limited and highly variable. Most strategies focused on developing and sharing educational materials, while administrative and systems-level interventions were largely absent. Standardized documentation of implementation strategies and outcomes could advance the field’s understanding of the effective development of interventions designed for implementation, encouraging faster uptake of effective interventions.